Impacts of RNA Mobility Signals on Virus Induced Somatic and Germline Gene Editing - Beernink, Bliss M.; Lappe, Ryan R.; Bredow, Melissa; Whitham, Steven A. (Frontiers in Genome Editing, 2022)
Viral vectors are being engineered to deliver CRISPR/Cas9 components systemically in plants to induce somatic or heritable site-specific mutations. It is hypothesized that RNA mobility signals facilitate entry of viruses or single guide RNAs (sgRNAs) into the shoot apical meristem where germline mutations can occur. Our objective was to understand the impact of RNA mobility signals on virus-induced somatic and germline gene editing in Nicotiana benthamiana and Zea mays. Previously, we showed that foxtail mosaic virus (FoMV) expressing sgRNA induced somatic mutations in N. benthamiana and Z. mays expressing Cas9. Here, we fused RNA mobility signals to sgRNAs targeting the genes encoding either N. benthamiana phytoene desaturase (PDS) or Z. mays high affinity potassium transporter 1 (HKT1). Addition of AtFT and AttRNAIle did not improve FoMV-induced somatic editing, and neither were sufficient to facilitate germline mutations in N. benthamiana. Maize FT homologs, ZCN16 and ZCN19, as well as AttRNAIle were found to aid somatic editing in maize but did not enable sgRNAs delivered by FoMV to induce germline mutations. Additional viral guide RNA delivery systems were assessed for somatic and germline mutations in N. benthamiana with the intention of gaining a better understanding of the specificity of mobile signal-facilitated germline editing. Potato virus X (PVX), barley stripe mosaic virus (BSMV), and tobacco rattle virus (TRV) were included in this comparative study, and all three of these viruses delivering sgRNA were able to induce somatic and germline mutations. Unexpectedly, PVX, a potexvirus closely related to FoMV, expressing sgRNA alone induced biallelic edited progeny, indicating that mobility signals are dispensable in virus-induced germline editing. These results show that PVX, BSMV, and TRV expressing sgRNA all have an innate ability to induce mutations in the germline. Our results indicate that mobility signals alone may not be sufficient to enable virus-based delivery of sgRNAs using the viruses, FoMV, PVX, BSMV, and TRV into cell types that result in germline mutations.